MEROMORF FUNCTIONS OF EVENTUAL ORDER WITH THE SET OF GREAT NUMBER VALIRON IMPERFECT VALUES - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A question of distributing of values of meromorf functions of eventual order is examined. It is got relatively complete description of great number of imperfect values in understanding of Valiron.